Endoscopic ultrasonography for preoperative staging of esophageal carcinoma. (3rd October 2017) - Shi, Haitao; Ma, Shiyang; Zhao, Ping; Jiang, Jiong; Cheng, Yan; Zhao, Juhui; Wang, Jinhai; Qiao, Zhe; Jiang, Jiantao; Li, Shaomin; Wu, Jie
Abstract: Objective: To evaluate the diagnostic value of endoscopic ultrasonography (EUS) in preoperative staging of esophageal carcinoma (EC). Material and methods: A total of 86 surgical patients with EC who were confirmed by endoscopy and biopsy underwent preoperative TN staging with EUS examination. The EUS findings were compared with surgical pathologic results. Results: The accuracy of EUS in T and N staging of EC was 82.6% and 84.9%, respectively. While determining whether EC invades the muscularis propria or outer membrane, EUS had the favorable sensitivity, specificity, positive predictive value and negative predictive value. The short-axis diameter of lymph nodes of 5mm had high sensitivity and negative predictive value to determine malignance with low specificity and positive predictive value. The short-axis diameter of 10mm presented the satisfactory sensitivity, specificity, positive predictive value and negative predictive value. Conclusion: EUS can accurately determine the TN staging of EC and provide a reliable basis for the treatment of EC.